Preparation method of konjac glucomannan-based hydrophobic biomass film
By purifying and deacetylation, and blending with other natural polymer materials, casting method assisted in defoaming treatment, the problems of excessive water solubility and poor mechanical properties of the konjac glucomannan film were solved, and a biomass film with high mechanical strength and good hydrophobicity were prepared.
Patent Information
- Application Number
- CN202411568089.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-05
AI Technical Summary
In the prior art, the film made of konjac glucomanan has problems such as excessive water solubility and poor mechanical properties, which are difficult to meet the needs of high mechanical strength and good hydrophobicity.
By purifying konjac glucomanan and carrying out a deacetylation reaction, its molecular structure was changed, combined with agar, plulandosac and glycerol, and casting method assisted in defoaming treatment, a konjac glucomananyl hydrophobic biomass film was prepared.
The prepared konjac glucomanyl hydrophobic biomass film has good hydrophobic properties, mechanical properties, improved strength and reduced water solubility, and is suitable for a variety of application scenarios.
Smart Images

Figure CN119684646A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and particularly relates to a method for preparing a konjac glucomannan-based hydrophobic biomass film. Background Art
[0002] Konjac glucomannan is a neutral, hydrophilic polysaccharide derived from konjac tubers. The genus Amorphophallus is rich in species, with as many as 163 species of Amorphophallus confirmed worldwide. As an excellent natural renewable resource, Konjac glucomannan is abundant in sources, easily degradable, and has excellent hydrophilicity, thickening, stability and other functional properties. It is widely used in the food production industry. Its hydrosol can form a film under appropriate conditions, and it has broad prospects for becoming a green packaging film.
[0003] Agar, also known as agarose, is extracted from the cell wall of red algae polysaccharide. It is a water-soluble polysaccharide with a polygalactoside structure, so it is a renewable and degradable green material. Agar has good gelation, film-forming and thickening properties. It is widely used in food, medicine, chemical industry, bioengineering and other fields.
[0004] Pullulan has high film-forming, adhesion, biocompatibility and degradability, certain mechanical strength, good film transparency, and good low oxygen permeability and oil resistance. Therefore, its products have very broad applications in food processing and packaging environmental protection, electronics, cosmetics and biomedicine.
[0005] In recent years, fossil resources have been decreasing. Therefore, research and development of new materials based on natural polymers has become one of the frontiers in the field of polymer science. Natural polymer materials are renewable and degradable and widely found in plants and animals. The research and development of new materials based on natural polymers can effectively reduce dependence on fossil resources, reduce environmental pressure, and conform to the concept of sustainable development.
[0006] Therefore, it is of great significance to develop an environmentally friendly composite film with high mechanical strength, good hydrophobicity, harmlessness, greenness and environmental protection. Summary of the invention
[0007] In order to solve the above problems, the present invention proposes a method for preparing a konjac glucomannan-based hydrophobic biomass film. The konjac glucomannan-based hydrophobic biomass film prepared by the method has good hydrophobic properties, mechanical properties, etc. The konjac glucomannan-based hydrophobic biomass film material adopts a degradable and biocompatible polymer material as a raw material, which helps to reduce dependence on fossil energy, promote the development of a circular economy, and contribute to environmental protection and sustainable development.
[0008] The present invention adopts the following technical solutions:
[0009] A method for preparing a konjac glucomannan-based hydrophobic biomass film comprises the following steps:
[0010] S1, purification: eluting konjac flour, drying, grinding and sieving to obtain konjac glucomannan;
[0011] S2, modification: the purified konjac glucomannan is fully stirred and mixed with an ethanol solution to form a homogeneous solution, and a sodium hydroxide solution is added to perform a deacetylation reaction to obtain deacetylated konjac glucomannan;
[0012] S3, film preparation: deacetyl konjac glucomannan is mixed with agar, pullulan and glycerol in a solvent, heated and stirred to form a film liquid, defoamed, and dried to obtain a konjac glucomannan-based hydrophobic biomass film formed by deacetyl konjac glucomannan, agar and pullulan.
[0013] Preferably, the konjac flour in step S1 is eluted in 65% ethanol for 4 hours, the elution is repeated three times, and dried in a 60° C. forced air oven, ground, and then sieved through a 100-mesh sieve to obtain konjac glucomannan.
[0014] Preferably, the concentration of ethanol in step S2 is 50%, and the mixture is stirred at 40°C.
[0015] Preferably, the concentration of sodium hydroxide in step S2 is 0.025-0.15 mol / L.
[0016] Preferably, in step S2, the stirring speed is 600 rpm and the stirring time is 24 h.
[0017] Preferably, in step S3, the mass ratio of deacetylated konjac glucomannan to agar is 3:1, the mass fraction of pullulan is 10%, and the mass fraction of glycerol in polysaccharide is 12.5%.
[0018] Preferably, the mixed solution in step S3 is stirred using an electric stirrer at a stirring speed of 800 rpm for 120 min.
[0019] Preferably, the konjac glucomannan-based hydrophobic biomass film in step S3 is formed by a tape casting method.
[0020] Preferably, the deacetylated konjac glucomannan, agar, pullulan and glycerol in step S3 are blended at 90°C.
[0021] Preferably, in step S3, the film liquid is heated in a forced air oven at a temperature of 60° C. and dried to obtain a konjac glucomannan-based hydrophobic biomass film.
[0022] After adopting the above technical solution, the present invention has the following advantages compared with the background technology:
[0023] 1. The materials such as konjac glucomannan, agar and pullulan used in the present invention are all natural macromolecular materials with degradability and biocompatibility. The purified konjac glucomannan has a more remarkable gel and a higher viscosity. The konjac glucomannan-based hydrophobic biomass film formed has a strong compactness and has good hydrophobicity, mechanical properties, etc.
[0024] 2. The present invention adopts the casting method assisted by vibration and temperature defoaming treatment to improve the uniformity of the composite film and reduce the influence of bubble leakage.
[0025] 3. The present invention aims to improve the performance of the film by changing the molecular structure of konjac glucomannan and removing the acetyl groups, thereby expanding its possibility in practical application.
[0026] 4. The composite film prepared by the present invention has high strength and good hydrophobicity, further expanding the application field of konjac glucomannan blended with other materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a Fourier transform infrared spectrogram of the deacetylated konjac glucomannan powder in Examples 1-6 of the present invention and the comparative example;
[0028] Figure 2 Graph showing the tensile strength of konjac glucomannan-based hydrophobic biomass films in Examples 1-6 of the present invention and Comparative Examples;
[0029] Figure 3 Graph showing elongation at break of konjac glucomannan-based hydrophobic biomass films in Examples 1-6 of the present invention and Comparative Examples;
[0030] Figure 4 It is a graph showing the water swelling rate of the konjac glucomannan-based hydrophobic biomass film in Examples 1-6 of the present invention and the comparative example;
[0031] Figure 5 The water solubility diagram of the konjac glucomannan-based hydrophobic biomass film in Examples 1-6 of the present invention and the comparative example;
[0032] Figure 6 The water vapor permeability graph of the konjac glucomannan-based hydrophobic biomass film in Examples 1-6 of the present invention and the comparative example;
[0033] Figure 7 The water contact angle diagrams of the konjac glucomannan-based hydrophobic biomass films in Examples 1-6 of the present invention and the comparative example. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0035] See also Figures 1 to 7 .
[0036] Prepare the raw materials: konjac flour, agar, pullulan, glycerol and sodium hydroxide. Among them, the purity of konjac flour is 98% (Hubei Qiangsen Konjac Technology Co., Ltd.), the purity of agar is 99.9% (Lanjieke Technology Co., Ltd.), the purity of pullulan is 99.9% (Shanghai MacLean Biochemical Technology Co., Ltd.), the purity of glycerol is 99% (Sinopharm Chemical Reagent Co., Ltd.), and the purity of sodium hydroxide is 99.5% (Sinopharm Chemical Reagent Co., Ltd.).
[0037] Example 1
[0038] Purification: The konjac flour was eluted in 65% ethanol for 4 hours, repeated 3 times, and finally rinsed with anhydrous ethanol. The konjac flour was dried in an oven at 60°C, ground, and sieved with a 100-mesh sieve to obtain konjac glucomannan.
[0039] Modification: 15g of purified konjac glucomannan was added to 150ml of 50% ethanol solution and shaken at 600rpm for 30min at 40℃. 7.5ml of 0.025mol / L sodium hydroxide solution was added to the suspension, adjusted to 600rpm, and reacted for 24h. After the reaction was completed, it was washed with 50%, 75%, and 95% ethanol, and finally washed with anhydrous ethanol. It was dried at 60℃ to prepare deacetylated konjac glucomannan with a deacetylation degree of 17.29%.
[0040] Film preparation: 0.675g of modified deacetylated konjac glucomannan, 2.025g of agar, 0.3g of pullulan and 0.375g of glycerol were weighed and placed in a three-necked flask, and 200ml of deionized water was added. The film solution was prepared by stirring at 800rpm for 120min at 90℃, and the film solution was poured into a beaker and ultrasonicated for 5min to remove bubbles. Each 50ml of sol was poured into a glass culture dish with a diameter of 90mm and waited for gel formation at room temperature. After gel formation, it was placed in a 60℃ oven to dry into a film.
[0041] Example 2
[0042] Purification: The konjac flour was eluted in 65% ethanol for 4 hours, repeated 3 times, and finally rinsed with anhydrous ethanol. The konjac flour was dried in an oven at 60°C, ground, and sieved with a 100-mesh sieve to obtain konjac glucomannan.
[0043] Modification: 15g of purified konjac glucomannan was added to 150ml of 50% ethanol solution and shaken at 600rpm for 30min at 40℃. 7.5ml of 0.05mol / L sodium hydroxide solution was added to the suspension, adjusted to 600rpm, and reacted for 24h. After the reaction was completed, it was washed with 50%, 75%, and 95% ethanol, and finally washed with anhydrous ethanol. It was dried at 60℃ to prepare deacetylated konjac glucomannan with a deacetylation degree of 10.07%.
[0044] Film preparation: 0.675g of modified deacetylated konjac glucomannan, 2.025g of agar, 0.3g of pullulan and 0.375g of glycerol were weighed and placed in a three-necked flask, and 200ml of deionized water was added. The film solution was prepared by stirring at 800rpm for 120min at 90℃, and the film solution was poured into a beaker and ultrasonicated for 5min to remove bubbles. Each 50ml of sol was poured into a glass culture dish with a diameter of 90mm and waited for gel formation at room temperature. After gel formation, it was placed in a 60℃ oven to dry into a film.
[0045] Example 3
[0046] Purification: The konjac flour was eluted in 65% ethanol for 4 hours, repeated 3 times, and finally rinsed with anhydrous ethanol. The konjac flour was dried in an oven at 60°C, ground, and sieved with a 100-mesh sieve to obtain konjac glucomannan.
[0047] Modification: 15g of purified konjac glucomannan was added to 150ml of 50% ethanol solution and shaken at 600rpm for 30min at 40℃. 7.5ml of 0.075mol / L sodium hydroxide solution was added to the suspension, adjusted to 600rpm, and reacted for 24h. After the reaction was completed, it was washed with 50%, 75%, and 95% ethanol, and finally washed with anhydrous ethanol. It was dried at 60℃ to prepare deacetylated konjac glucomannan with a deacetylation degree of 22.91%.
[0048] Film preparation: 0.675g of modified deacetylated konjac glucomannan, 2.025g of agar, 0.3g of pullulan and 0.375g of glycerol were weighed and placed in a three-necked flask, and 200ml of deionized water was added. The film solution was prepared by stirring at 800rpm for 120min at 90℃, and the film solution was poured into a beaker and ultrasonicated for 5min to remove bubbles. Each 50ml of sol was poured into a glass culture dish with a diameter of 90mm and waited for gel formation at room temperature. After gel formation, it was placed in a 60℃ oven to dry into a film.
[0049] Example 4
[0050] Purification: The konjac flour was eluted in 65% ethanol for 4 hours, repeated 3 times, and finally rinsed with anhydrous ethanol. The konjac flour was dried in an oven at 60°C, ground, and sieved with a 100-mesh sieve to obtain konjac glucomannan.
[0051] Modification: 15g of purified konjac glucomannan was added to 150ml of 50% ethanol solution and shaken at 600rpm for 30min at 40℃. 7.5ml of 0.1mol / L sodium hydroxide solution was added to the suspension, adjusted to 600rpm, and reacted for 24h. After the reaction was completed, it was washed with 50%, 75%, and 95% ethanol, and finally washed with anhydrous ethanol. It was dried at 60℃ to prepare deacetylated konjac glucomannan with a deacetylation degree of 28.56%.
[0052] Film preparation: 0.675g of modified deacetylated konjac glucomannan, 2.025g of agar, 0.3g of pullulan and 0.375g of glycerol were weighed and placed in a three-necked flask, and 200ml of deionized water was added. The film solution was prepared by stirring at 800rpm for 120min at 90℃, and the film solution was poured into a beaker and ultrasonicated for 5min to remove bubbles. Each 50ml of sol was poured into a glass culture dish with a diameter of 90mm and waited for gel formation at room temperature. After gel formation, it was placed in a 60℃ oven to dry into a film.
[0053] Example 5
[0054] Purification: The konjac flour was eluted in 65% ethanol for 4 hours, repeated 3 times, and finally rinsed with anhydrous ethanol. The konjac flour was dried in an oven at 60°C, ground, and sieved with a 100-mesh sieve to obtain konjac glucomannan.
[0055] Modification: 15g of purified konjac glucomannan was added to 150ml of 50% ethanol solution and shaken at 600rpm for 30min at 40℃. 7.5ml of 0.125mol / L sodium hydroxide solution was added to the suspension, adjusted to 600rpm, and reacted for 24h. After the reaction was completed, it was washed with 50%, 75%, and 95% ethanol, and finally washed with anhydrous ethanol. It was dried at 60℃ to prepare deacetylated konjac glucomannan with a deacetylation degree of 35.28%.
[0056] Film preparation: 0.675g of modified deacetylated konjac glucomannan, 2.025g of agar, 0.3g of pullulan and 0.375g of glycerol were weighed and placed in a three-necked flask, and 200ml of deionized water was added. The film solution was prepared by stirring at 800rpm for 120min at 90℃, and the film solution was poured into a beaker and ultrasonicated for 5min to remove bubbles. Each 50ml of sol was poured into a glass culture dish with a diameter of 90mm and waited for gel formation at room temperature. After gel formation, it was placed in a 60℃ oven to dry into a film.
[0057] Example 6
[0058] Purification: The konjac flour was eluted in 65% ethanol for 4 hours, repeated 3 times, and finally rinsed with anhydrous ethanol. The konjac flour was dried in an oven at 60°C, ground, and sieved with a 100-mesh sieve to obtain konjac glucomannan.
[0059] Modification: 15g of purified konjac glucomannan was added to 150ml of 50% ethanol solution and shaken at 600rpm for 30min at 40℃. 7.5ml of 0.15mol / L sodium hydroxide solution was added to the suspension, adjusted to 600rpm, and reacted for 24h. After the reaction was completed, it was washed with 50%, 75%, and 95% ethanol, and finally washed with anhydrous ethanol. It was dried at 60℃ to prepare deacetylated konjac glucomannan with a deacetylation degree of 42.41%.
[0060] Film preparation: 0.675g of modified deacetylated konjac glucomannan, 2.025g of agar, 0.3g of pullulan and 0.375g of glycerol were weighed and placed in a three-necked flask, and 200ml of deionized water was added. The film solution was prepared by stirring at 800rpm for 120min at 90℃, and the film solution was poured into a beaker and ultrasonicated for 5min to remove bubbles. Each 50ml of sol was poured into a glass culture dish with a diameter of 90mm and waited for gel formation at room temperature. After gel formation, it was placed in a 60℃ oven to dry into a film.
[0061] Comparative Example
[0062] Purification: The konjac flour was eluted in 65% ethanol for 4 hours, repeated 3 times, and finally rinsed with anhydrous ethanol. The konjac flour was dried in an oven at 60°C, ground, and sieved with a 100-mesh sieve to obtain konjac glucomannan.
[0063] Film preparation: 0.675g of modified deacetylated konjac glucomannan, 2.025g of agar, 0.3g of pullulan and 0.375g of glycerol were weighed and placed in a three-necked flask, and 200ml of deionized water was added. The film solution was prepared by stirring at 800rpm for 120min at 90℃, and the film solution was poured into a beaker and ultrasonicated for 5min to remove bubbles. Each 50ml of sol was poured into a glass culture dish with a diameter of 90mm and waited for gel formation at room temperature. After gel formation, it was placed in a 60℃ oven to dry into a film.
[0064] Performance Test:
[0065] (1) The dried deacetylated konjac glucomannan powder samples in the comparative example and Examples 1-6 were ground and mixed with KBr powder, and then placed in a blast oven to dry for 5 minutes, and then placed in a mold to be pressed into thin sheets. -1 In the wave number range, 32 scans were performed at room temperature with air as the background and a resolution of 4 cm -1, and the data were baseline corrected. -1 and 1614cm -1 The absorption peak at , as the degree of deacetylation increases, weakens, indicating that the stretching vibration and hydrogen bonding of C=O are reduced, and the deacetylation modification is successful, such as Figure 1 As shown, Figure 1 The deacetylation degrees of the comparative example, example 1, example 2, example 3, example 4, example 5 and example 6 are 0%, 10.07%, 17.29%, 22.91%, 28.56%, 35.28% and 42.41%, respectively.
[0066] (2) The film samples obtained in the comparative example and Examples 1-6 were placed in a constant temperature and humidity environment at 25°C and 50% relative humidity for a period of time, and then the film was cut into a rectangular size of 10×100 mm. The tensile strength and elongation at break of the composite film were tested using a universal testing machine. The composite film had the highest tensile strength of 85.47 MPa when the degree of deacetylation was 28.56%. Figure 2 When the deacetylation degree is 35.28%, the highest elongation at break is 14.86%. Figure 3 shown.
[0067] (3) The water solubility and water swelling properties of the composite films obtained in the comparative example and Examples 1-6 were tested: the balanced composite film was cut into small pieces of 2×2 cm, dried at 60°C to constant weight, and the mass was recorded as m1. The small pieces of film were soaked in water at room temperature for 24 hours, and the moisture on the surface of the film was absorbed with filter paper after being taken out. The mass was recorded as m2, and the water swelling rate = (m2-m1) / m1. The swollen small pieces of film were dried in an oven at 50°C to constant weight, and the mass was recorded as m3 after being taken out. The water solubility = (m1-m3) / m1. The prepared composite film had the lowest swelling rate of 465.37% when the degree of deacetylation was 35.28%, such as Figure 4 When the deacetylation degree is 28.56%, the water solubility is the lowest, which is 15.90%. Figure 5 shown.
[0068] (4) Cover the film samples obtained in the comparative example and Examples 1-6 on a 50mL conical flask filled with anhydrous CaCl2 and seal the flask mouth with glue, place it in a dryer containing 1000mL saturated sodium chloride solution at 25°C and 75% RH, weigh it every 1 hour until the mass is balanced, and take out the conical flask in the prescribed order to weigh the mass every 24 hours. (The saturated water vapor pressure of saturated sodium chloride solution at 25°C is 2.63kPa) WVP = (Δm·d) / (A·Δt·ΔP). Where Δm is the weight increase per unit penetration time, d is the thickness of the film, A is the area of the flask mouth, Δt is the penetration time interval, and ΔP is the water vapor pressure difference on both sides of the film. The lowest water vapor permeability is 0.9849g·m when the deacetylation degree is 28.56%. -1 h - 1 Pa -1 .
[0069] (5) The film samples obtained in the comparative example and Examples 1-6 were cut into 5×50 mm strips and placed on a horizontal movable table. Water (5 μL) was dropped on the film surface using a 10 uL micro syringe. After waiting for 30 seconds, the contact angle between water and the film was measured. The prepared composite film had the highest water contact angle of 102.5° when the degree of deacetylation was 35.28%. Figure 7 shown.
[0070] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a konjac glucomannan-based hydrophobic biomass film, characterized in that: The steps include: S1, purification: eluting konjac flour, drying, grinding and sieving to obtain konjac glucomannan; S2, modification: the purified konjac glucomannan is fully stirred and mixed with an ethanol solution to form a homogeneous solution, and a sodium hydroxide solution is added to perform a deacetylation reaction to obtain deacetylated konjac glucomannan; S3, film preparation: deacetyl konjac glucomannan is mixed with agar, pullulan and glycerol in a solvent, heated and stirred to form a film liquid, defoamed, and dried to obtain a konjac glucomannan-based hydrophobic biomass film formed by deacetyl konjac glucomannan, agar and pullulan.
2. The method for preparing a konjac glucomannan-based hydrophobic biomass film according to claim 1, wherein: The konjac flour in step S1 is eluted in 65% ethanol for 4 hours, the elution is repeated three times, and dried in a 60° C. forced air oven, ground, and sieved through a 100-mesh sieve to obtain konjac glucomannan.
3. The method for preparing a konjac glucomannan-based hydrophobic biomass film according to claim 1, wherein: The concentration of ethanol in step S2 is 50%, and the mixture is stirred at 40°C.
4. The method for preparing a konjac glucomannan-based hydrophobic biomass film according to claim 1, wherein: The concentration of sodium hydroxide in step S2 is 0.025-0.15 mol / L.
5. The method for preparing a konjac glucomannan-based hydrophobic biomass film as claimed in claim 1, wherein: In step S2, the stirring speed is 600 rpm and the stirring time is 24 h.
6. The method for preparing a konjac glucomannan-based hydrophobic biomass film according to claim 1, wherein: In step S3, the mass ratio of deacetyl konjac glucomannan to agar is 3:1, the mass fraction of pullulan is 10%, and the mass fraction of glycerol in polysaccharide is 12.5%.
7. A method for preparing a konjac glucomannan-based hydrophobic biomass film as claimed in claim 1, characterized in that: In step S3, the mixed solution was stirred using an electric stirrer at a stirring speed of 800 rpm for 120 min.
8. A method for preparing a konjac glucomannan-based hydrophobic biomass film as claimed in claim 1, characterized in that: In step S3, the konjac glucomannan-based hydrophobic biomass film is formed by a casting method.
9. The method for preparing a konjac glucomannan-based hydrophobic biomass film according to claim 1, wherein: In step S3, the deacetylated konjac glucomannan, agar, pullulan and glycerol are blended at 90°C.
10. The method for preparing a konjac glucomannan-based hydrophobic biomass film according to claim 1, characterized in that: In step S3, the membrane liquid is heated in a forced air oven at a temperature of 60° C. and dried to obtain a konjac glucomannan-based hydrophobic biomass film.
Citation Information
Patent Citations
Konjac glucomannan sticking membrane used for sanitary travel sleeping bag and preparation method for konjac glucomannan sticking membrane
CN104927074A
Method for preparing high-toughness konjac glucomannan preservative film
CN105801890A
Konjac glucomannan high-temperature resistant food packaging film and preparation method thereof
CN110305372A
Polysaccharide / protein composite film with high barrier property and preparation method thereof
CN110920159A
Super-moisture-absorption substrate film containing konjac glucomannan and hydroxy propyl cellulose
CN115926261A
Cited By
High-toughness konjac-based biological polysaccharide composite film as well as preparation method and application thereof
CN120944153A
High-toughness konjac-based biological polysaccharide composite film and preparation method and application thereof
CN120944153B